Environmental drivers of shifts on microbial traits in sites disturbed by a large-scale tailing dam collapse - Batista, Éder Rodrigues; Carneiro, Joana Junqueira; Araújo Pinto, Flávio; dos Santos, Jessé Valentim; Carneiro, Marco Aurélio Carbone (The Science of the total environment, 2020)
This study aimed to assess the most affected traits related to microbial ecophysiology and activity and investigate its relationships with environmental drivers in mine tailings spilled from the Fundão dam at disturbed sites across Gualaxo do Norte river, Minas Gerais, Brazil. The mine tailings are characterized by increased pH value, silt percentage, and bulk density, while clay percentage, organic carbon (Corg), total nitrogen (Nt), and moisture contents are reduced. Microbial biomass, enzymatic activities (arylsulfatase, β-1,4-glucosidase, acid and alkaline phosphatases), and the total microbial activity potential (FDA hydrolysis) were generally lower in tailings compared to undisturbed reference soil (Und). Enzyme-based indexes (GMea, WMean, and IBRv2) showed microbial communities with significantly lower degradative efficacy in the tailings than Und in all sites (R2 ≥ 0.94, p < 0.001). Non-metric multidimensional scaling and distance-based redundancy analysis revealed that microbial communities exhibited significant differentiation (R2 adjusted = 0.73, p = 0.0001) between mine tailings and Und over the different studied sites, which was strongly influenced by changes on physicochemical properties (pH, Corg and Nt contents, the predominance of small-sized particles of silt, and bulk density) and the presence of Se, Cr, Fe, and Ni, even at low concentrations. Our study suggests that the physicochemical properties and the presence of low bioavailable concentrations of heavy metals in dam tailings promote shifts on microbial communities through reductions in the C storage and biogeochemical cycling of nutrients by these communities compared to those in undisturbed reference soils surrounding and, therefore, has negative implications for the ecosystem functioning. Conceptual diagram of differences in microbial traits among disturbed conditions and undisturbed reference soils after the large-scale Fundão dam collapse across Gualaxo do Norte river, Brazil. AMF, arbuscular mycorrhizal fungi. [Display omitted] •Effects of Fundão dam tailings on microbial traits of disturbed areas were assessed.•Microbial biomass and activity at tailings were generally low.•Enzyme-based indexes were successfully used to measure environmental quality.•Physicochemical properties had high importance in shifting microbial traits at tailings.